2017
DOI: 10.1016/j.livsci.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of abomasal conditions (pH, pressure and temperature) in healthy and diarrheic dairy calves using a wireless ambulatory capsule

Abstract: A B S T R A C TThis study investigated abomasal luminal parameters in healthy and diarrheic calves by using a wireless ambulatory capsule (WAC). The acetaminophen absorption test (APAT) was used to determine abomasal emptying rate. Four healthy and five diarrheic female Holstein-Friesian calves (age < 14 days) were included in the study. For APAT, calves were fed 2 L of milk replacer containing 50 mg acetaminophen/kg body weight, and blood samples were taken during a 12-h period afterward. Concomitantly, a WAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our results suggest that heat stress may also delay abomasal emptying in preweaning calves when FR is increased. It is worth noting that other stressors, such as diarrhea, have also been reported to delay abomasal emptying in calves (Kirchner et al, 2015;Hildebrandt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that heat stress may also delay abomasal emptying in preweaning calves when FR is increased. It is worth noting that other stressors, such as diarrhea, have also been reported to delay abomasal emptying in calves (Kirchner et al, 2015;Hildebrandt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Marshall et al () postulated that the time to reach maximum serum AP levels was the most accurate index to describe AER. Further, lower abomasal pressure data and higher abomasal temperature data were described in diarrhoeic calves than in healthy calves (Hildebrandt et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Kirchner et al () recently described delayed abomasal emptying during diarrhoea in suckling calves. According to these findings, a delay in abomasal emptying and changes in intraluminal conditions, such as temperature, were confirmed by using an acetaminophen absorption test (APAT) and a telemetric device in diarrhoeic calves (Hildebrandt et al, ). Impaired abomasal motility might be a risk factor for bacterial mal‐fermentation processes facilitating the production of short‐chain fatty acids (SCFA).…”
Section: Introductionmentioning
confidence: 96%
“…An extreme example for a poor animal model with respect to the investigation of the gastroretentive potential is the dairy calve. In a recent study, we found gastric residence times for telemetric capsules that exceeded the power supply of the capsules (>5 days) [124]. Such examples demonstrate that comparable dimensions of the gastrointestinal segments are not necessarily indicative of the comparable transit behavior of dosage forms.…”
Section: Characterization Of Gastroretentive Dosage Formsmentioning
confidence: 97%